Current state of agricultural units: as a phenomenon and complexity - RÍOS PÉREZ, Juan David; CRISSIEN BORRERO, Tito José; RAMÍREZ MOLINA, Reynier Israel; VILLALOBOS ANTÚNEZ, José Vicente; LAY RABY, Nelson David; RAMOS MARQUEZ, Yanelis Margarita (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This research identifies the current state of the Atlantic department’s agricultural units, allowing knowledge of weaknesses and strengths. A subjective interpretation, a central point for knowledge and understanding of the systemic - holistic reality of the study variable, is used as a methodology, based on the reflective analytical approach, with respect to the phenomenon and complexity, studied in the current theoretical references and classical disciplinary intellectual production. The findings show poverty figures, below the regional average, above the national average. The need to study the internal and external environment is concluded, considering technological progress and integration of the public and private of sector.